Bacillus subtilis를 이용한 발효 감자 칩의 감자 품종에 따른 아크릴아마이드 저감화 비교 - 여성순(Seoungsoon Yeo); 임상은(Sangeun Yim); 진용익(Yong-Ik Jin); 장동칠(Dong-Chil Chang); 장윤혁(Yoon Hyuk Chang); 이영승(Youngseung Lee); 정윤화(Yoonhwa Jeong); 김미숙(Misook Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
Acrylamide is a probable human carcinogen and can be formed during frying of starchy foods. The objective of this study was to investigate the effects of acrylamide reduction in storage potato chips by fermentation of Bacillus subtilis and compare its usefulness with four different cultivars of storage potatoes (Goeun, Atlantic, Saebong, and Jinsun). Potato slices were fermented by B. subtilis at $37^{°}C$ for 0, 2, and 4 h and fried at $180^{°}C$ for 115 s. The total sugar contents of the fermented potato slices did not change compared to the control. However, reducing sugar contents increased in the fermentation solution containing potato slices. Asparagine contents of Saebong and Jinsun potato slices decreased with fermentation time. Color values of the fermented potato chips were improved compared to those of non-fermented potato chips. The highest $L^*$ value was found in Saebong (57.4), followed by Goeun (56.7), Jinsun (52.5), and Atlantic (48.8) after 4 h of fermentation. Potatoes stored for 240 days generated considerable amounts of acrylamide, ranging from 4.99 to 10.38 ppm, after frying. Four hours of fermentation reduced acrylamide formation in all potato chips. The lowest acrylamide content was found in Saebong (0.77 ppm), followed by Jinsun (1.21 ppm), Goeun (1.76 ppm), and Atlantic (4.09 ppm). In conclusion, fermentation of storage potatoes by B. subtilis can effectively lower acrylamide formation during frying of potato chips. 본 연구에서는 240일간 저장한 네 가지 품종의 감자를 Bacillus subtilis로 발효한 후 제조한 감자 칩의 아크릴아마이드 함량과 색도 변화를 알아보고자 하였다. B. subtilis에 의한 단시간 발효는 모든 품종의 감자 슬라이스로부터 유리된 환원당 제거에 효과적이었으나 총당 함량 감소에는 영향을 미치지는 않았다. 또한, 새봉과 진선 감자 슬라이스 내 존재하는 아스파라긴 함량도 감소하였다. 이러한 결과는 복합적으로 감자 칩의 아크릴아마이드 생성량과 색 형성에 영향을 미쳤다. 대서를 제외한 나머지 세 품종은 모두 83% 이상의 아크릴아마이드 감소율을 보였다. 따라서 본 연구는 B. subtilis에 의한 단시간 발효를 통하여 저장감자를 가공식품으로 활용할 수 있는 방안을 제시하고 있다.